THE ROLE of MYCORRHIZAL INOCULUM AND POTASSIUM FERTILIZER ON THE GROWTH OF Zea mays L. UNDER WATER STRESS - Salman , Nariman D.; Hameed, Saja Sabih (Diyala Agricultural Sciences Journal, 2017)
A pot experiment was conducted at the lath –house of the Department of Soil Sciences and Water Resources, College of Agriculture, University of Baghdad during the fall season of 2013. Sandy loam texture soil was used to study the effect of mycorrhiza and potassium addition on the growth of corn plant under water stress. Three potassium levels were used control (K0), 100 (K1) and 200 (K2) Kg h-1. Mycorrhiza inoculation was used with three treatments of inoculation (without inoculation (M0), with mycorrhiza, Gloums spp. (M1) and inoculation with roots infected by mycorrhiza (M2) and treatments were three water levels 40% (W1), 60% (W2) and 80% (W3) available water and three replicates by using a Complete Randomized Design (CRD). Results showed that significant. Results showed that inoculation with mycorrhiza (M1) significantly increase the shoot and root dry weight which was 31.39 g pot-1 and 10.02 g pot-1 and leaf, root area 90.59 cm2, 127.36 cm2, respectively, compared with M0 and M2 treatments. The addition of potassium with inoculation by mycorrhiza led to mitigation the high water stress on growth of plant through there's interactional work. Best result was achieved due to the triple interaction among water stress, mycorrhiza and potassium, where W1M1K2 treatment showed significant increment in the dry weight of shoot system, leaves surface area with increase ratios as 15.8, 8.4%, respectively, compared with W3M0K0 treatment